Animal normativity - Danon, Laura (2019)
Many philosophers think that human animals are the only normative creatures. In this paper, I will not provide reasons against such a claim, but I will engage in a related task: delineating and comparing two defationary accounts of what non-human animal normativity could consist in. One of them is based on Hannah Ginsborg's notion of primitive normativity and the other on my conjecture that some creatures may have frst-order robust “ought-thoughts”, composed by secondary representations about how things should be or about how one should act. Once I have sketched both models, I will focus on identifying some cognitive differences between creatures merely having primitive normativity and those also having robust ought-thoughts. Finally, I will draw a few tentative remarks on the kind of empirical evidence that would suggest that an animal has one or another of these two kinds of normativity.